Low Myo‐inositol indicating astrocytic damage in a case series of neuromyelitis optica. Issue 2 (4th September 2013) - Ciccarelli, Olga; Thomas, David L.; De, Enrico; Wheeler‐Kingshott, Claudia A. M.; Kachramanoglou, Carolina; Kapoor, Raj; Leary, Siobhan; Matthews, Lucy; Palace, Jacqueline; Chard, Declan; Miller, David H.; Toosy, Ahmed T.; et al.
<x xml:space="preserve">Abstract</x> Astrocytic necrosis is a prominent pathological feature of neuromyelitis optica (NMO) lesions and is clinically relevant. We report 5 NMO‐related cases, all with longitudinally extensive lesions in the upper cervical cord, who underwent cervical cord 1H‐magnetic resonance spectroscopy. Lower myo‐inositol/creatine values, suggesting astrocytic damage, were consistently found within the NMO lesions when compared with healthy controls and patients with multiple sclerosis (MS), who showed at least 1 demyelinating lesion at the same cord level. Therefore, the in vivo quantification of myo‐inositol may distinguish NMO from MS. This is an important step toward developing imaging markers for clinical trials in NMO. Ann Neurol 2013;74:301–305